2017
DOI: 10.1016/j.triboint.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of loading on the friction and interface microstructure of lubricated steel tribopairs

Abstract: In this study, the tribological behavior and interfacial evolution of GCr15/Mild steel tribopairs lubricated by inorganic sodium metaphosphate was investigated under different applied loads at 800 °C. The results show that sodium metaphosphate lubricates the contact effectively at the load ranging from 5 to 30 N, with higher loads causing increased friction and wear. A layer of glassy phosphate film formed between the contacts is responsible for the improved tribological performance. FIB/TEM and XRD analysis r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The O s -Fe bond can also be cleaved and form iron oxide nanoparticles which will be digested by phosphate lubricant. The digestion of iron oxide by polyphosphate tribofilm at 800 1C has been proposed by Cui et al 80 As the structure of the iron/iron oxide nanoparticle is different from standard crystalline oxide, 81 the interactions of alkali phosphates and iron-based nanoparticles are worth further investigation, particularly the competition between alkali and iron ions inside phosphate tribofilm. Generally, the alkali metal plays a role as a network modifier which reduces the P-O-P bridging bonds and ionically interacts with terminal oxygen atoms.…”
Section: Discussionmentioning
confidence: 99%
“…The O s -Fe bond can also be cleaved and form iron oxide nanoparticles which will be digested by phosphate lubricant. The digestion of iron oxide by polyphosphate tribofilm at 800 1C has been proposed by Cui et al 80 As the structure of the iron/iron oxide nanoparticle is different from standard crystalline oxide, 81 the interactions of alkali phosphates and iron-based nanoparticles are worth further investigation, particularly the competition between alkali and iron ions inside phosphate tribofilm. Generally, the alkali metal plays a role as a network modifier which reduces the P-O-P bridging bonds and ionically interacts with terminal oxygen atoms.…”
Section: Discussionmentioning
confidence: 99%
“…In the molten state polyphosphates interact with the steel surface, which leads to the high adhesion of film. Tribological study at 800 °C showed [25] that sodium metaphosphate reduces coefficient of friction by 49 %. It is assumed that this is due to the formation of short-chain amorphous compounds of the types NaFePO 4 and Na 3 Fe(PO 4 ) 2 .…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…At the same time, steel formation at high temperature is a complex process, which is accompanied by thermal, microstructural, physical and chemical transformations in the surface layer of articles [26]. The attention of researchers is concentrated in these systems mainly on the tribological characteristics of polyphosphates [23][24][25]. However, the ability of polyphosphates to protect steel surface from corrosion requires a comprehensive approach when choosing components of technological greasing.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The result found that a thin layer of phosphate film with a thickness of several hundred nano-metres adsorbing on the wear track of the disc, and such layer of lubrication film evolves with temperature and affect the lubrication behaviour. The authors also had studied the lubrication behaviour of sodium metaphosphate inorganic polymer under different loads at 800 C. 19 The results revealed that there exists a thick phosphate film adhering on the steel tribopair for all the tested loads, and iron oxide nano-particles were found to be distributed in the polymeric mixed Na-Fe phosphate. The effect of hot rolling process parameters on the lubricating behaviour of glassy phosphoric polymers, and found that high temperature and large rolling reduction promote the introduction of lubricants and the reduction of rolling force.…”
Section: Introductionmentioning
confidence: 99%